Implementasi Ijarah dan Ijarah Muntahia Bit-Tamlik (IMBT) dalam Perbankan Syariah Di Indonesia - Miko Polindi (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2016)
Implementation of Ijarah and Ijarah Muntahia Bit-Tamlik (IMBT) in Islamic banking in Indonesia. Islamic banking in Indonesia has been growing significantly it is shown from the Performa of increasing the number of Islamic financial institutions in Indonesia. The products of Islamic banking has also been increasing with variety type of contracts and more competitive to opt the market and adjustable according to the people need. Among the popular products on Islamic Banking which do not exist in conventional banks are Ijarah and Ijarah Muntahia Bit-Tamlik (IMBT), in this case the author found that the contract of IMBT is a solution in providing the low cost of Loans for Housing to the community, but it is still rarely used in Islamic Banking, because of the lack of knowledge and practical exploration on the IMBT contract.